Análise dos efeitos da exigência de respostas em escolhas de autocontrole - Poço, Thiago Francisco Peppe Del (2019)
Self-control is a theoretical model proposed by Skinner (1953/2007) and studied experimentally in a paradigm of choice by several authors (Rachlin & Green, 1972; Siegel and Rachlin 1995, among others). Mazur (2012) introduces a response requeriment called "pretentative" before the point of choice between impulsivity and self-control components. The objective of the present study was to evaluate, like Mazur (2012), the effect of the quantity of work on choice responses, with humans, trying to evaluate if the requirement of previous responses (pretentative) to choice responses between alternatives that produce larger later reinforcers (self-control) and smaller and immediate reinforcers (impulsiveness) would establish self-control choices. For the experiment, intrinsic reinforcers (cartoon videos) were used because of the different results presented in researchs that used points as conditioned reinforcers. Participated 10 adults, who were selected for the Experimental Sessions, for having a pattern of impulsive responses, were asked to choose between an smaller sooner (impulsive) and a larger later (self-control) component after requesting (pretentative) responses. For the Experimental Sessions they were exposed to a concurrent scheme in which, for the first link (pretentatives), a lower or higher response requirement was selected prior to selection using reinforcement schemes in an ABAB design (FR1, FR40, FR1 and FR40). For the second link, they chose between a larger later component or a smaller sooner component. Four of the 10 participants reversed the preference of impulsive choice to self-controlled when introduced to response requirements. Three of the four participants who reversed the preference presented an increase in the distribution of the responses in the self-control component between the first and second FR 40, also there is no decrease in the self-control responses when the FR1 conditions are introduced. By introducing high demand for responses (FR 40), participants who have reversed their preference for self-control do not return to an impulsive pattern, as observed in Matos and Micheletto (2013). The dispersion in the choices between the impulsive and selfcontrolled component is similar to that identified in the studies of Forzano (2014) and Navarick (1996), in which there was no concurrent schedule linked with a fixed ratio variable